Gain and loss of phototrophic genes revealed by comparison of two Citromicrobium bacterial genomes. - Qiang Zheng; Rui Zhang; Paul C M Fogg; J Thomas Beatty; Yu Wang; Nianzhi Jiao (PLoS ONE)
Proteobacteria are thought to have diverged from a phototrophic ancestor, according to the scattered distribution of phototrophy throughout the proteobacterial clade, and so the occurrence of numerous closely related phototrophic and chemotrophic microorganisms may be the result of the loss of genes for phototrophy. A widespread form of bacterial phototrophy is based on the photochemical reaction center, encoded by puf and puh operons that typically are in a 'photosynthesis gene cluster' (abbreviated as the PGC) with pigment biosynthesis genes. Comparison of two closely related Citromicrobial genomes (98.1% sequence identity of complete 16S rRNA genes), Citromicrobium sp. JL354, which contains two copies of reaction center genes, and Citromicrobium strain JLT1363, which is chemotrophic, revealed evidence for the loss of phototrophic genes. However, evidence of horizontal gene transfer was found in these two bacterial genomes. An incomplete PGC (pufLMC-puhCBA) in strain JL354 was located within an integrating conjugative element, which indicates a potential mechanism for the horizontal transfer of genes for phototrophy.